Gastrointestinal parasite fauna of gentoo penguins (Pygoscelis papua) from the Peninsula Munita, Bahia Paraiso, Antarctica - Fredes, Fernando; Madariaga, Cristián; Raffo, Eduardo; Valencia, José; Herrera, Marcela; Godoy, Claudia; Alcaíno, Héctor (2007)
Publicación ISI Email : fredes@uchile.cl